2004
DOI: 10.1002/jnr.20299
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of Brn‐3a POU protein with p53 in a population of neuronal progenitor cells is associated with differentiation and protection against apoptosis

Abstract: The Brn-3a transcription factor is critical for survival and differentiation of sensory neurons derived from neural crest cells (NCC). Interaction of Brn-3a with p53 results in differential effects on target gene expression, which profoundly affects fate of neuronal cells. Here we demonstrate colocalization of p53 in a subset of Brn-3a-positive NCC-derived cells fated for the sensory neuronal lineage. The distinct morphology of Brn-3a/p53-coexpressing cells suggested a differentiated neuronal cell type, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…We first investigated whether Brn-3a and p73 are co-expressed in a developmentally relevant model by undertaking co-immunostaining studies in primary cultures of neural crest cells (NCC) that give rise to sensory neurons, and are known to express Brn-3a. 26,27 As expected, Brn-3a was expressed in two populations of NCC-derived cells. Figure 1a shows that the larger flattened differentiated cells with neurite outgrowth express both p73 and Brn-3a whereas Figure 1b shows that the smaller, rounded undifferentiated Brn-3a expressing NCC 26 are negative for p73.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…We first investigated whether Brn-3a and p73 are co-expressed in a developmentally relevant model by undertaking co-immunostaining studies in primary cultures of neural crest cells (NCC) that give rise to sensory neurons, and are known to express Brn-3a. 26,27 As expected, Brn-3a was expressed in two populations of NCC-derived cells. Figure 1a shows that the larger flattened differentiated cells with neurite outgrowth express both p73 and Brn-3a whereas Figure 1b shows that the smaller, rounded undifferentiated Brn-3a expressing NCC 26 are negative for p73.…”
supporting
confidence: 64%
“…26,27 As expected, Brn-3a was expressed in two populations of NCC-derived cells. Figure 1a shows that the larger flattened differentiated cells with neurite outgrowth express both p73 and Brn-3a whereas Figure 1b shows that the smaller, rounded undifferentiated Brn-3a expressing NCC 26 are negative for p73. Figure 1c and Supplementary Figure S1A show that when co-localized in NCC, both p73 and Brn-3a show nuclear expression.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, Wnt7b was found to be one of the new putative p53 target genes during NGF-mediated PC12 neuronal differentiation [86]. Studies in neuronal cells have suggested that the interaction of p53 with the neuron-specific and pro-differentiation TF BRN3A facilitates a shift of p53 transcriptional activity from cell death to neuronal differentiation [87]. As there are approximately 12 000 neuronal activity-regulated enhancers that are bound by the general transcriptional co-activator CBP/p300 in a neuronal activity-dependent manner, the function of CBP/p300 at enhancers may be to recruit RNAPII together with p53, as activity-regulated RNAPII binding to thousands of enhancers has been observed [50].…”
Section: Cell-intrinsic Epigenetic Mechanisms Targeted By Cell-cycle mentioning
confidence: 99%
“…62 However, a switch in POU TFs from BRN1/2 to BRN3a occurs in post-mitotic cells. 63 HMGA2. High mobility group A2 (HMGA2) is a chromatin associated protein that potentiates the activity of TFs.…”
Section: Gli-2 Gli-3 (Zfp)mentioning
confidence: 99%